Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/eji.200636606
|View full text |Cite
|
Sign up to set email alerts
|

MSK regulate TCR‐induced CREB phosphorylation but not immediate early gene transcription

Abstract: Stimulation of the T cell receptor activates the ERK1/2 and p38 mitogen-activated protein kinase (MAPK) cascades. We demonstrate that TCR stimulation also activates the mitogen-and stress-activated kinases (MSK) downstream of ERK1/2 and p38 in both a T cell line and primary peripheral T cells. MSK1/2-knockout mice were found to have normal numbers of T cells in the thymus, and development of these cells appeared unaffected. Using naive T cells and T lymphoblasts from MSK1/2-knockout mice, it was found that MSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
(65 reference statements)
3
25
0
Order By: Relevance
“…In most cell types the MAPK-dependent transcription of nur77 requires the phosphorylation of CREB by MSKs [35]. However, in T cells TCR-induced nur77 transcription, while dependent on MAPK signalling, is independent of MSKs and CREB phosphorylation [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cell types the MAPK-dependent transcription of nur77 requires the phosphorylation of CREB by MSKs [35]. However, in T cells TCR-induced nur77 transcription, while dependent on MAPK signalling, is independent of MSKs and CREB phosphorylation [49].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was reverse-transcribed using iScript (BioRad), and real-time PCR carried out using Sybrgreen based detection methods (BioRad). Primers for 18s, nur77, nor1 and egr3 have been described previously [35,49]. Primer sequences for ERK5, IL-2, IL-4, IL-13, IFN-g and IkBa are listed in Table 3.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments based on in situ 3 H-thymidine and BrdU incorporation showed that 2-3% of epidermal LC are cycling (5) and that murine epidermal LC express the Ki67 proliferation-associated antigen (6). Several electron microscopic observations of LC undergoing mitosis within human epidermis have also been reported (7). Experimental data obtained in mice have suggested that under steady-state conditions the efflux of LC to local lymph nodes would be balanced by LC divisions within the epidermis, whereas under conditions severely depleting epidermal LC (such as UV-radiation), LC precursors would be recruited from the peripheral blood (8).…”
Section: Introductionmentioning
confidence: 98%
“…Following activation, MSK1 ⁄ 2 are able to phosphorylate transcription factors such as CREB and ATF1 (3,(7)(8)(9)(10). Through activation of these transcription factors, MSK1 ⁄ 2 regulate the expression of a number of specific immediate early genes such as c-fos, junB and egr1 (6,10,11).…”
Section: Introductionmentioning
confidence: 99%